PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCING (NPF) DAN PENEMPATAN DANA PADA BANK INDONESIA TERHADAP PROFITABILITAS (STUDI EMPIRIS PADA BANK UMUM SYARIAH TAHUN 2012-2015) - Fatimatuzzahro Fatimatuzzahro (Universitas Islam Malang, 2017)
This study aims to determine the effect of Third Party Funds, Non Performing Financing and Placement of Funds at Bank Indonesia to Profitability of Sharia Commercial Banks for the Period 2012-2015. The data used in this study is secondary data, while the sample used is a sharia commercial bank registered in BI period 2012-2015. The Sampling technique was done by Purposing Sampling method. The sample of this research is 11 companies with 4 years observation. Data analysis was done by using multiple linier regression method. The result of this study indicate that. (1) Third Party Funds has no effect on Profitability. (2) Non Performing Financing has a significant negative effect on Profitability. (3) Placement of Funds at Indonesia Banks has a significant negative effect on Profitability.